(untitled) (Al-Academy, 2025)
The current study dealt with the relationship between the strategy of guided imagination and the development of creative thinking, and the problem of the current research was summarised by the question: What is the strategy of guided imagination and its impact on the development of creative thinking? The current research objective was to identify the strategy of guided imagination and its impact on the development of creative thinking among students of art education. The first chapter also included a definition of the importance of research, the limits of research and hypotheses and the definition of the terms contained therein. The second chapter, represented by the theoretical framework, included two topics, the first: dealing with the strategy of guided imagination, while the second topic dealt with creative thinking, while the third chapter included all research procedures, while the fourth chapter included the results of the research, conclusions, recommendations and proposals, and the researchers reached a number of results, including: The researcher used the T-test (T-test) for two interrelated samples to verify the validity of this hypothesis, so the calculated T value was (5,120) which is greater than the table T value of (2.00) and with a degree of freedom (41), which indicates that there is a statistically function difference and in favour of the experimental group in the test of creative thinking dimensionally